2019
DOI: 10.3390/ani9110984
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Methionine Sources on Performance and Slaughter Characteristics of Broilers

Abstract: Simple SummaryThe increasing public demand for efficient, sustainably produced poultry meat with simultaneous optimization of animal welfare is calling for amendments in meat production. A starting point to meet this demand consists of complete diets for broilers with reduced crude protein content, supplemented with higher amounts of crystalline amino acids. This ensures sufficient nutritional supply and decreased nitrogen excretion for environmental relief. To optimize the performance and health, despite the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 55 publications
4
6
0
Order By: Relevance
“…No differences (p > 0.05) were observed for different types of amino acid on the carcass characteristics of broilers. This finding confirmed the reports of earlier researchers [31,41] who observed that the type of methionine had no effect on live weight, carcass weight, after skin removal, eviscerated weight and chest weight because L-Met is directly absorbed in the body and DL-Met, MHA is first converted into L-Met and then absorbed in the body. Also, Drazbo et al [42] found that the source of dietary methionine had no effect on carcass yield or breast muscle quality.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…No differences (p > 0.05) were observed for different types of amino acid on the carcass characteristics of broilers. This finding confirmed the reports of earlier researchers [31,41] who observed that the type of methionine had no effect on live weight, carcass weight, after skin removal, eviscerated weight and chest weight because L-Met is directly absorbed in the body and DL-Met, MHA is first converted into L-Met and then absorbed in the body. Also, Drazbo et al [42] found that the source of dietary methionine had no effect on carcass yield or breast muscle quality.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the cystine deficiency results in the reduction in the recovery of breast meat and also decreases the extent of feathering. Our finding of no effects of the sources of methionine on the starter phase of broilers is supported by other researchers [22,31] who observed that L-Met and DL-Met did not affect growth performance due to conversion of DL-Met into L-Met. It seems that lower metabolization of D-amino acid due to the lower amount of D-amino acid oxidase in young broilers may reduce the utilization of higher amounts of DL-Met, which leads to metabolic stress and inhibition of body weight gain in the starter phase.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…No significant differences were found in these forms on health, performance, and the quality composition of breast meat of birds. L-methionine caused the highest protein and the lowest fat content in meat (Ullirich et al 2019). Altering levels of amino acids in the diet may affect performance and health status in poultry.…”
Section: Advances In Delivery Of Nutraceuticalsmentioning
confidence: 99%
“…The deficiency or excess of methionine or cysteine in its diet affect a chicken's performance [5]. The deficiency of methionine leads to reduced growth performance, immune functioning, and increased abdominal fat proportions and feather pecking [6][7][8][9]. The methionine requirement can be fulfilled only by methionine; however, the cysteine requirement can also be satisfied with methionine.…”
Section: Introductionmentioning
confidence: 99%